The role of the humanities in shaping the value orientations of prospective offi cers in a military university - Shabanov, Anatoliy Григорьевич; Laptev, Alexey Анатольевич (Известия Саратовского университета. Новая серия: Акмеология образования. Психология развития)
The relevance of the research is determined by the modern realities of transforming the value and semantic sphere of our society (primarily of the youth), which is associated with the preservation and strengthening of traditional spiritual and moral values of Russia. The value choice of a person remains one of the key issues in modern pedagogical axiology. The values which are crucial for a person, especially at the stage of one’s professional development, are of great signifi cance. Hhumanities play a special role in shaping value orientations of university students, including students of military universities. In modern conditions, there is no balance between the humanitarian subjects. This can lead to a decrease in their popularity among students and weakening of the humanitarian training in military education. Purpose of the study is to substantiate the role of the humanities in developing value orientations of prospective offi cers in a military university. Results: it has been found out that updating the axiological potential of the humanities, as well as complementing the content structure of the academic courses with traditional Russian values and the experience of the special military operation, contribute to the formation of students’ conscious attitude to the defense of the Motherland and personal responsibility for its fate. The study proves the effi cacy of introducing the new course “Foundations of the Russian Statehood” into the curriculum of a military university. Main conclusions: teaching the humanities in a military university is a key factor in the spiritual and moral development of military specialists. The study shows that the course “Foundations of the Russian Statehood” contributes to improving the content and effi cacy of the educational process in military universities. Practical significance: the results of the study can be used in organizing the educational process of military universities in the fi eld of humanitarian training of prospective offi cers.